Fighting Poverty with Sheep in Armenia: The Role of Hope - Weichbrodt, Louisa Joline; Justus Liebig University Giessen (My University, 2026)
Half of the world's population lives in poverty, yet eradicating poverty remains the first Sustainable Development Goal by 2030. Studies evaluating poverty traps and livestock often overlook the role of hope in their analyses, a factor that has recently been recognised as vital in combating poverty. Non-Governmental Organisations implement livestock transfer projects to help families escape poverty and restore hope. To understand the role of hope in these projects, a qualitative approach with interviews was employed, combined with observations of multidimensional poverty indicators to reveal participants' experiences of hope and changes in poverty. The study found that hope is essential for participants' responses to the project and, consequently, supports their exit from poverty. Levels of hope significantly influence perceptions and in turn, actions during participation. Moreover, individual hope was enhanced through livestock transfers, affecting goals, mood, and perception of the future. Subtle changes in multidimensional poverty related to housing and health expenditure planning were also observed. Additionally, development projects can nurture hope by improving mental health, addressing multiple dimensions of poverty, and actively supporting participants' aspirations. Policies can influence both external and internal constraints on poverty and foster hope: firstly, by providing structural grounds for hope; secondly, by informing about available opportunities; and thirdly, by encouraging and supporting aspirations. The government can use policies to promote hopefulness. The fact remains that people living in poverty are not necessarily hopeless. Further research could offer quantitative insights into hope within development contexts. Overall, recognising the role of hope is crucial for designing holistic and effective development projects.
Keywords: hope; development economics; poverty; livestock; Armenia; development cooperation; ddc:330; ddc:630